Perlawanan Pedagang Kaki Lima dan Dampaknya Terhadap Kebijakan Ekonomi Lokal di Kota Tanjungpinang. - Dedek Hardiyanti; Mellyana Candra; Norsyakina Norsyakina; Ririn Murtiani (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
In Tanjungpinang, street vendors' (PKL) resistance to government policy demonstrates the complex dynamics of informal economy management. The purpose of this research is to gain an understanding of the different types of PKL resistance, the methods they use, and how it impacts on local economic policy. Relevant scientific documents were analyzed using a literature study approach. The results show that street vendors not only carry out physical resistance, but also carry out symbolic and cultural actions. As a result, organized social movements emerge. The government's top-down policies often cause tensions, so discussions and cooperation are needed to create more inclusive and participatory policies. Economic empowerment, spatial flexibility, and the development of public-private partnerships are some of the suggested solutions. It is hoped that this research will make a significant contribution to building a policy model that is more responsive to the social realities of society, especially with regard to vulnerable groups.